An approach towards wavelet transform based multiclass object classification - Khare M.; Kushwaha A.K.S.; Srivastava R.K.; Khare A. (My University, 2025)
Object classification is an important problem in computer vision, in which multiclass object classification is more difficult one in comparison to single class object classification. In this paper, we proposed a new method for multiclass object classification based on discrete wavelet transform. We have used discrete wavelet transform coefficients as a feature of object, because of its multi-resolution property. We have used multiclass support vector machine as a classifier for classification of objects. The proposed method has been tested on own dataset prepared by authors of this paper. We have tested the proposed method on multiple levels of discrete wavelet transform. Quantitative evaluation results shows that the proposed method gives better performance for multiclass object classification at higher level of discrete wavelet transform and other state-of-the-art methods. © 2013 IEEE.